Compaixão e Terror em Poética 1449b (Nuntius Antiquus, 2008)
This paper is a brief commentary on the words “fear” and “pity”, which define the tragedy in Aristotle’s Poetics, and its occurrence in tragic texts. The aim is to get a statistical occurrence of these terms in order to clarify Aristotle’s understanding of this poetical style, and its use by playwrights of the fifth century BC.